A new direction to athletic performance: Understanding the acute and longitudinal responses to backward running - Uthoff, A.; Oliver, J.; Cronin, J.; Harrison, C.; Winwood, P. (Sports Medicine, 2018)
Backward running (BR) is a form of locomotion that occurs in short bursts during many overground field and court sports. It has also traditionally been used in clinical settings as a method to rehabilitate lower body injuries. Comparisons between BR and forward running (FR) have led to the discovery that both may be generated by the same neural circuitry. Comparisons of the acute responses to FR reveal that BR is characterised by a smaller ratio of braking to propulsive forces, increased step frequency, decreased step length, increased muscle activity and reliance on isometric and concentric muscle actions. These biomechanical differences have been critical in informing recent scientific explorations which have discovered that BR can be used as a method for reducing injury and improving a variety of physical attributes deemed advantageous to sports performance. This includes improved lower body strength and power, decreased injury prevalence and improvements in change of direction performance following BR training. The current findings from research help improve our understanding of BR biomechanics and provide evidence which supports BR as a useful method to improve athlete performance. However, further acute and longitudinal research is needed to better understand the utility of BR in athletic performance programs.